PEMANFAATAN SIRSAK DAN NANAS DALAM PEMBUATAN VELVA - RARA ANIRA; VONNY SETIARIES JOHAN; YELMIRA x YELMIRA ZALFIATRI (Universitas Riau, 2019)
Velva is a frozen dessert made from fruits which has low fat and high fiber. The purpose of this research wasto obtain the best combination of soursop and pineapple puree for quality and sensory velva produced. Thisstudy used a complete randomized design with five treatments and three replications, resulting in 15 experimentalunits. The treatment research were SN1: soursop puree and pineapple puree (90:10), SN2: soursoppuree and pineapple puree (80:20), SN3: soursop puree and pineapple puree (70:30), SN4: soursop pureeand pineapple puree (60:40), SN5: soursop puree and pineapple puree (50:50). Parameters observed in thisstudy included pH, overrun, melting time, crude fiber content, vitamin C and assessment sensory (descriptiveand hedonic). The best treatment was a treatment with soursop puree and pineapple puree (50:50) with 4,68pH, 16,73 % overrun, 10,43 minutes melting time, 4,79 % crude fiber and 18,14 mg vitamin C . The result ofthe descriptive test of the velva from the best treatment was yellow color, scented with soursop and pineapplefruit flavor, pinapple taste, textured very soft and overall acceptance the panelists like the velva produced.